PERSPEKTIF MASYARAKAT DALAM MENGHADAPI TRANSFORMASI PELAYANAN PUBLIK NEW NORMAL DI KOTA MADIUN - Dandi Darmadi; Bariq Rakhmadian; Afrian Dwi Candranira; Aqshal Bagoes Avanzar Noegraha (Journal Publicuho, 2021)
Studies on the transformation of public services, especially in the era New Normal, not only focus on digitalization efforts but also relate to culture and crises that require social restrictions and solutions to local approaches are not comprehensive in analyzing qualitatively and from two government perspectives, namely Department of Occupation and Civil Registry (Dispendukcapil) of Madiun City and Society. This article aims to describe and analyze people's perspectives on transforming public services carried out by the Madiun Municipal Dispendukcapil. This research was conducted by observing Madiun City people who take care of the Madiun City Dispendukcapil and studying literature. The results showed that the community was still not adaptive to the service transformation carried out, but this was because the dissemination of information from the Dispendukcapil was not widespread, so that people still came to the service office, besides that the limited ability of the digital platform by the community was also an obstacle. The government's strategy that must be carried out in improving services in the era new normal is to consider the risks of ASN in serving, especially the provision of ASN with complete personal protective equipment. It requires collaborative leadership where all sectors must be carried out as well as unlimited creativity and responsiveness.